Peranan Metode Pembelajaran terhadap Minat dan Prestasi Belajar Al-Qur’an Hadis - Khalijah, Wan Nur; Jannah, Miftahul; Rehan, Hafiz Zurahmah; Yohana; Yohani (Al-Wasathiyah: Journal of Islamic Studies, 2023)
Writing this journal is to determine the role of learning methods on interest and achievement in learning the Qur'an and Hadith. The low quality of student learning is caused by two factors, namely internal and external. Factors that influence the learning process and the results of student internalization include responsiveness to learning, desire and drive to learn, and focus on learning. While external factors include teachers as learning coaches, learning facilities and infrastructure, assessment policies, and social status around students. school and home, and the school curriculum. Learning what gets attention is more acceptable than learning what doesn't, and it's not trivialized or irrelevant. Of course, in the case of interest, people with an interest in a particular area might find it easier to learn. Of course learning is carried out and culminates in school achievement which describes success and success in learning. The achievement of good learning affects many things, including the learning methods used by the teacher. Learning success is achieved when all factors support it, such as using interesting methods that can be used as a bridge to achieve competency. Keywords: